PERBEDAAN KOMITMEN ORGANISASI DITINJAU DARI TIPE WORK-LIFE BALANCE PADA GURU SMP NEGERI DI SIDOARJO - Fitria Nasywa, Suluh; Olievia Prabandini Mulyana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examined differences in organizational commitment in terms of work-life balance types among public junior high school teachers in Sidoarjo Regency. A comparative quantitative design with purposive sampling involved 334 teachers. Data from validated work-life balance and organizational commitment scales were analyzed using an Independent Sample T-Test. The results showed a significant difference between Active Balance and Beneficial Balance types (t(307.9) = -7.409; p < 0.001). Teachers with Beneficial Balance demonstrated higher organizational commitment than those with Active Balance. These findings indicate that work-life balance typology specifically the interaction between job demands and resources plays a key role in shaping teachers' organizational commitment. This study contributes by showing that a typological approach provides a richer understanding of organizational commitment variation.